Biomarkers in phase I–II chemoprevention trials: lessons from the NCI experience - Szabo, Eva (Ecancermedicalscience, 2015)
Early phase clinical trials are an essential component of chemopreventive drug development to identify signals of drug efficacy that can subsequently be explored definitively in phase III trials. Whereas phase I trials focus on safety and identification of optimal dose and schedule for cancer prevention, phase II trials focus on intermediate endpoints that are variably related to cancer development. The United States National Cancer Institute supports a programme devoted to early phase cancer prevention clinical trials. The experience, along with the benefits and limitations of the range of biomarker endpoints used in these studies, are reviewed here.